(untitled) (Economics and region, 2023)
Economic security is a component of Ukraine’s national security. It is the foundation for the implementation of the strategic directions of the state’s development and is responsible for the formation of finances and a stable economy, which should not be influenced by either internal or external factors. Already now, a theoretical analysis of possible threats to the economic security of territorial communities in the conditions of military operations is relevant, in order to solve and avoid a number of problems, taking into account all the gaps, after analyzing the international experience and its implementation in Ukraine. The study of international experience can provide information on countering threats to the economic security of territorial communities in Ukraine. Their solution will contribute to ensuring fair opportunities for the equality of human capital, improving the ecological state of the environment, social protection, and food security. The purpose of the article is a theoretical analysis of possible threats to the economic security of territorial communities in the conditions of military operations and ways of predicting and avoiding them, taking into account international experience. The materials of the research are: scientific works of scientists, legislation, project activity investigating threats to the economic security of territorial communities in the conditions of military operations. When writing the article, techniques of the logical method, legal methods, systematic method, method of comparison, structural-functional method were used. As a result of the scientific research, a number of recommendations in the practical sphere, generalizations, theoretical proposals, based on the analysis of the works of scientists who researched the specified problems, were proposed. The analysis of threats to the economic security of territorial communities in the context of military operations, taking into account domestic and international research, their systematization and the study of ways to prevent the impact on the development of the economy contribute to a further deeper study of the problem and the introduction of effective and efficient solutions in practice.